Manufacture of Nanofibers for Wound Dressing Applications from Sea Cucumber and Curcuma longa, Turmeric sp. - Rahmawati; Wida Fatma Sari; Atina; Parmin Lumban Toruan (University of Jember, 2025)
The skin is the topmost layer that safeguards the body and can be vulnerable to injuries, such as cuts. Turmeric and sea cucumber are recognized for their effectiveness in healing wounds. The research used natural polymers such as turmeric and sea cucumber, while the synthetic polymer used was polyvinyl alcohol (PVA). Electrospinning equipment is used to produce the nanofibres. The variables investigated in this study were the concentrations of PVA, turmeric, and sea cucumber. Gamat and curcuma are proven to accelerate wound healing, but no literature explains whether they are compatible with PVA in making nanofibres. The nanofibres were analysed using scanning electron microscopy (SEM). The most optimal nanofiber composition for wound dressing applications is PVA with a concentration of 12%, turmeric 2%, and curcuma 0.5%.